Incorporation of international virtual teams as a complementary component to the traditional educational model (2019)
The model of virtual teams in higher education is being increasingly recognized as a phenomenon of great value to students about learning environments in the real world (Hsieh, Jang, Hwang, & Chen, 2011). Meanwhile, today’s environment requires from educational institutions dedicated to instruction undergraduate and graduate students, a rapid evolution of their models of teaching in order to conform to the same speed with which all fields transform in knowledge. This paper discusses the inclusion of virtual teams in the top-level educational models, meaning that incorporation as an option applies to all educational institutions, and above all, to their learning traditional structures. In this sense, the document includes analysis of relevant academic literature and data collected through interviews, conducted at six higher education faculty, who work in virtual teams schemes globally.